Alejandro Duque Amusco, Donde rompe la noche, Calle del Aire 133, Sevilla, Renacimiento, 2015 (segunda edición ampliada y definitiva), 83 pp. - Balcells Doménech, José María (Lectura y signo, 2016)
Reseña